Adapting to The Pandemic COVID-19: Smart City Implementation in Blitar City - Rizqi Bachtiar; Dimas Aufar Dwi Cahya (Journal of Governance, 2022)
COVID-19 seriously hitting most countries worldwide is an alarming issue affecting the mindset of the Indonesian government. Many studies have revealed that the outbreak has forced the government to make some adjustments by seeking smart solutions that are effective and efficient for public services, which has brought the government to the concept of a smart city. Departing from this background, this research aims to investigate how Blitar City is struggling to adapt to the situation by adjusting to the Smart City implementation. This research found that, guided by qualitative research methodology and the Smart City theoretical framework, the desire for changes in terms of public services from citizens is relatively high. However, the lack of a legal basis for the smart city in Blitar City seems to hinder the objective. Furthermore, there is a vague understanding of the concept that is hampered by some local agencies (Dinas) and civil servants. Therefore, local regulation relating to the concept is required to ensure the implementation of smart cities in Blitar City. The Readiness of all actors in Blitar City also needs upgrading in order to maintain the long-term Smart City implementation at a local level.